(untitled) - Broom, Donald M. (Cambridge, UK, 2003)
Donald Broom argues that morality and the central components of religion are of great value, and presents two central ideas. He asserts that morality has a biological foundation and has evolved as a consequence of natural selection, and that religions are essentially the structures supporting morality. Many philosophers and theologians write about morality and its origins without reference to biological processes such as evolution. Likewise, biologists discuss phenomena of importance to human morality and religion without taking account of the thoughts of others on these subjects.
Keywords: Ethics, Evolutionary,Sociobiology; Religious aspects; Sinh học xã hội,Đạo đức, tiến hóa; Khía cạnh tôn giáo